Dear Santa : a novel - Macomber, Debbie (Ballatine Books, 2021)
Feeling low after her boyfriend cheated on her, Lindy Carmichael heads home to Wenatchee, Washington for Christmas where her mother encourages her to write a grown-up letter to Santa which ultimately brings her hope and joy.